What’s love got to do with jealousy? - Fernandez, Ana Maria; Barbato, Maria Teresa; Cordero, Belen; Acevedo, Yvone (Frontiers in Psychology, 2023)
Romantic love and jealousy, seemingly at odds, actually share evolutionary functions that support close relationships. Both emotions serve cooperative purposes within the context of natural selection. Love addresses adaptive challenges related to pair bonding, cooperation, and offspring protection, while jealousy arises when a valuable cooperative relationship, vital for descendants or a close romantic bond, is threatened. Therefore, love and romantic jealousy converge in the adaptive domain of preserving a romantic pair bond. Love can be understood in two ways: as attachment to significant others formed over a lifetime and as affective dependence. Research involving 332 from a single´s and committed individual´s sample indicates a positive correlation between attachment and jealousy as stable traits, aligning with existing literature. However, the correlation between attachment and love as a measure of dependence is low and non-significant. Notably, in the sample of single participants, jealousy is associated with love. The discussion highlights the importance of expanding the functional understanding of love and jealousy as complementary components of our human emotional repertoire. Future research could explore attachment as a relational trait and love as a specific affection for a romantic partner, potentially shedding light on the functional intricacies of jealousy.